Jihad in the west : the rise of militant salafism - Egerton, Frazer, 1977- (Cambridge : Cambridge University Press, 2011)
'Militant Salafism is one of the most significant movements in politics today. Unfortunately its significance has not been matched by understanding. To begin to address this knowledge deficit this book argues that, rather than the largely unhelpful pursuit of individual'root causes' offered in much of the literature, we would be better served by looking at the factors that have enabled and facilitated a particular political imagery. That political imagery is one that allows individuals to conceive of themselves as integral members of a global battle waged between the forces of Islam and the West, something that lies at the heart of militant Salafism. Frazer Egerton shows how the ubiquity of modern media and the prevalence of movement have allowed for a transformation of existing beliefs into an ideology supportive of militant Salafism against the West amongst Western Muslims'--
Machine generated contents note: Introduction; 1. Mad Mullah or freedom fighter? What is a militant Salafist?; 2. What is wrong with these people?; 3. Taking us everywhere: the role of the political imagery; 4. (Hyper)media and the construction of the militant community; 5. Movement: from actual to ideological; 6. Why me? The role of broader narratives and intermediaries; Conclusion.
Includes bibliographical references (p. 165-218) and index.
Keywords: Jihad; Salafiyah; Terrorism -- Religious aspects -- Islam; Islamic fundamentalism